Stable gas-liquid chromatography column for fatty acid analysis. - Hansen, L B (1977)
A mixed gas-liquid chromatography column of FFAP and Apolar-7CP has excelelnt thermal stability and shows excellent characteristics for the separation of the methylesters of fatty acids from Salmonella enteritidis call wall lipids.